A randomized clinical trial comparing the impact of different oral hygiene protocols and sealant applications on plaque, gingival, and caries index scores - Zingler, Sebastian; Pritsch, Maria; Wrede, Dirk J.; Ludwig, Björn; Bister, Dirk; Kneist, Susanne; Lux, Christopher J. (European journal of orthodontics, 2014)
This prospective randomized clinical trial investigated the impact of different tooth brushing strategies and sealant application on patients with fixed appliances: plaque, gingival, caries index scores, periodontal parameters, microbial, and molecular biological parameters were assessed.
Published: 03 July 2013
Gesehen am 09.09.2020